A 6-month analysis of training-intensity distribution and physiological adaptation in Ironman triathletes - Neal, C. M.; Hunter, A. M.; Galloway, S. D. R. (Journal of Sports Sciences, 2011)
In the present study, we analysed the training-intensity distribution and physiological adaptations over a 6-month period preceding an Ironman triathlon race. Ten athletes (mean ± s: age 43 ± 3 years, mass 78.3 ± 10.3 kg, stature 1.79 ± 0.05 m) participated in the study. The study consisted of three training periods (A, B, C), each of approximately 2 months' duration, and four testing weeks. Testing consisted of incremental tests to exhaustion for swimming, cycling and running, and assessments for anthropometry plus cardiovascular and pulmonary measures. The lactate threshold and the lactate turnpoint were used to demarcate three discipline-specific, exercise-intensity zones. The mean percentage of time spent in zones 1, 2, and 3 was 69 ± 9%, 25 ± 8%, and 6 ± 2% for periods A-C combined. Only modest physiological adaptation occurred throughout the 6-month period, with small to moderate effect sizes at best. Relationships between the training volume/training load and the training-intensity distribution with the changes in key measures of adaptation were weak and probably reflect differences in initial training status. Our results suggest that the effects of intensity distribution are small over short-term training periods and future experimental research is needed to clarify the potential impact of intensity distribution on physiological adaptation.